ORGANIZATIONAL COMMITMENT AND WORK ENVIRONMENT MATTER TO ENHANCE JOB PERFORMANCE OF TEACHERS - Muhammad Nawaz; Dr. Muhammad Naveed Jabbar; Sidrah Pervaiz Butt (International Journal of Contemporary Issues in Social Sciences, 2024)
In modern era it has been realized like other organizations the educational institutions has become business organization where institutions render the supportive working environment to fulfil the organizational commitment for the elevation of job performance of the academicians. The main objective of this research was to examine the effect of organizational commitment and working environment on job performance. The population of this study was public secondary school teachers from Gujranwala whereas, 266 respondents were selected as sample through simple random sampling technique. For data collection structured questionnaires were administered by applying survey method. SPSS software was used to evaluate the research hypotheses. The findings indicated a significant effect of organizational commitment and working environment on job performance. Moreover, organizational commitment had more significant effect on job performance than that of working environment. This research is a landmark for institutional management to assume various approaches and practices for the enhancement of employees’ performance.